The female athlete - Frank, R. (Elsevier, 2021)
Of all the important factors that must be considered when assessing and treating an athlete, the impact of patient sex is perhaps the most critical, yet historically has often been neglected. The "same injury" in a male patient may present differently, sometimes in subtle ways, than in a female patient and may require a different treatment approach. The Female Athlete, edited by Dr. Rachel Frank, provides concise, expert coverage of the ways in which common sports medicine injuries present in female patients versus male patients, describing recent literature analyzing sex differences in injury patterns and available treatment options.